Everlasting - Woodiwiss, Kathleen E. (New York : William Morrow, 2007)
Follows the relationship between Berengaria, who is forced into marriage with a nefarious squire, and her beloved Raven, a Scottish soldier determined to save her from an evil fate.
Keywords: Forced marriage -- Fiction; Middle Ages -- Fiction; Love stories